Understanding and measuring emotions in technology-rich learning environments. (December 2020) - Lajoie, Susanne P.; Pekrun, Reinhard; Azevedo, Roger; Leighton, Jacqueline P.
Abstract: Technology-rich learning environments (TREs) play an increasingly important role for 21st century education, and the emotions learners experience in these environments are pivotal for their cognitive and affective learning gains. The contributors to this special issue address the importance of understanding and measuring emotions in TREs as a mechanism for fostering learning. In particular, the special issue situates this research with a systemic review and meta-analysis of the literature on emotions in TREs. Following this review empirical research is presented on measuring emotions in the context of learning with TREs in multiple domains, including medicine, history, and mathematics. These researchers use concurrent measures to capture students' cognitive, metacognitive and affective processes before, during, and after solving problems, documenting the complex role of such processes as individuals and groups learn with technology. The special issue concludes with two commentaries that point the way to next steps in this field of research. Highlights: Technology-rich learning environments (TRES) play a role in 21st century education. Emotions learners experience in TRES are pivotal for learning gains. Examples of measuring emotions in the context of learning with TREs are provided. Individual and group emotions are explored in the context of TRES.